English teachers’ perceptions of project-based language learning in secondary schools in Ningbo China - Jun, Yong Xu; Jin, Kuan Kok; Sagaya Raj a/l A Rajoo Gerard,; Poh, Chua Siah (Penerbit Universiti Kebangsaan Malaysia, 2017)
The perceptions of language teachers on project-based language learning (PBLL) is important as negative perceptions will affect the adoption and promotion of PBLL in a particular English learning context. The educational culture of basic English education in mainland China is teacher, classroom, textbook and examination-oriented which is opposite to the principles of conducting PBLL, which may cause negative perceptions among language teachers of PBLL. Therefore, this study adopts a mixed methods approach in the investigation of English teachers’ perceptions of PBLL in 9 secondary schools in Ningbo China. A questionnaire survey and semi-structured interviews were employed to gather the relevant data from 265 English teachers. The results of data indicate that: (1) PBLL can be promoted in secondary schools in Ningbo further due to the positive perceptions of PBLL of most of English teachers, but it is proper for English teachers to take PBLL as a supplement to the traditional classroom instruction in English; (2) the educational culture may affect the perceptions of language teachers of PBLL to some extent, but it is not a determinant factor; (3) the social environment factor may affect language teachers’ perceptions of PBLL, such as the economic development and the English education quality of a district.